Efficient Gathering and Transport of Associated Multiphase Gases in Accordance with the Dynamics of Gas Resources - Ismayilova, F.B. (Herald of Azerbaijan Engineering Academy, 2022)
The article analizes the issues of gathering and transport of condensing associated gases, taking into account the flow rate and pressure of gas pumping. It is shown that the issues of efficient use (utilization) of associated gases are mainly related to the problem of their transport in a multiphase state. In the article it is also shown ways to improve the efficiency of gathering and transport of associated gases.